2016
DOI: 10.1111/fwb.12718
|View full text |Cite
|
Sign up to set email alerts
|

Lake‐type‐specific seasonal patterns of nutrient limitation in German lakes, with target nitrogen and phosphorus concentrations for good ecological status

Abstract: Summary Eutrophication is a global environmental problem that leaves many lakes with impaired ecological status. Human activity has increased the total concentrations of both nitrogen and phosphorus in aquatic systems, but their relative influence on phytoplankton biomass is uncertain. Their action as alternative limiting resources complicates assessment of their relative influence and disagreement may be in part due to seasonal shifts and lake‐type‐specific differences in the prevalence of limitation by nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 49 publications
4
51
2
Order By: Relevance
“…To assess the relative importance of phosphorus and nitrogen as limiting nutrients, the N:P ratio was used. As an indicator for discriminating between N and P limitation, we used the DIN:TP ratio, which has been identified as the best predictor for phytoplankton nutrient limitation (Bergstr€ om, 2010;Dolman, Mischke, & Wiedner, 2016;Ptacnik, Andersen, & Tamminen, 2010). Above a ratio of 3.4, phytoplankton usually shifts from nitrogen to phosphorus limitation.…”
Section: Data Preparation and Statistical Analysismentioning
confidence: 99%
“…To assess the relative importance of phosphorus and nitrogen as limiting nutrients, the N:P ratio was used. As an indicator for discriminating between N and P limitation, we used the DIN:TP ratio, which has been identified as the best predictor for phytoplankton nutrient limitation (Bergstr€ om, 2010;Dolman, Mischke, & Wiedner, 2016;Ptacnik, Andersen, & Tamminen, 2010). Above a ratio of 3.4, phytoplankton usually shifts from nitrogen to phosphorus limitation.…”
Section: Data Preparation and Statistical Analysismentioning
confidence: 99%
“…Depending on the lake type, even lower values of 0.02-0.06 mg L À1 have been suggested in order to limit algae growth and to reach a good status. 3 Conventional techniques for P removal include precipitation with di-or trivalent metal ions and biological removal. Low residual phosphate concentrations are achieved with high doses of occulants.…”
Section: Introductionmentioning
confidence: 99%
“…At the pH PZC of the adsorbent the building of two different surface complexes is proposed by Hiemstra. 13 A binuclear bidentate complex with exchange of two ligands resulting in^(FeO) 2 Si(OH) 2 and a mononuclear monodentate complex^(FeOHFeO)Si(OH) 3 . At low concentrations and low pH values silicate is mostly present as monomers, whereas the amount of oligomeric and polymeric silicates increases steeply at circum-neutral pH values.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus (P) was at one time thought to be the main nutrient limiting phytoplankton biomass in the majority of lakes (Schindler, ); however, since the 1970s, empirical and experimental studies have demonstrated that nitrogen (N) is also important in many lakes (see Lewis & Wurtsbaugh, ; Sterner, for review). In cross‐lake analyses, phytoplankton biovolume is more closely related to N when N:P ratios are low (Dolman & Wiedner, ) and conditions indicative of N limitation seem to predominate in shallow polymictic and riverine lakes (Dolman, Mischke, & Wiedner, ). In lakes that are identified as N limited, N loading reduction could be an ecologically meaningful way to improve water quality; however, concerns exist that compensatory N 2 ‐fixation by cyanobacteria (Nostocales) could render N load reduction measures ineffective (Schindler, , ; Schindler et al, ).…”
Section: Introductionmentioning
confidence: 99%